CHALLENGES AND TRENDS OF FINTECH DEVELOPMENT IN THE BANKING, INSURANCE AND FUND MARKETS (INNOVATIVE ECONOMY, 2024)
Lutsiv B.L., Chaikovskyi Ya.I. CHALLENGES AND TRENDS OF FINTECH DEVELOPMENT IN THE BANKING, INSURANCE AND FUND MARKETSPurpose. The aim of the article is to study of the role of FinTech in the processes of digital transformation of banking with the identification of challenges and trends for the banking system of Ukraine.Methodology of research. The following research methods were used to achieve the goal: analysis and synthesis, abstract and logical – to characterize the stages of digital transformation in banking, substantiation of digital technologies that will contribute to the reform of the banking sector; monographic and comparative – for the study of the legislative field in the introduction of financial technologies in the banking sector of Ukraine.Findings. It has been established that the development of financial technologies (FinTech) significantly affects the banking business, causing both positive changes and new challenges, which significantly transforms the banking business. The essential characteristics of digital technologies that are reforming the banking sector are revealed, as well as an assessment of the advantages and risks brought by digitalization to the banking sector, which made it possible to determine its trends and challenges, namely: the introduction of digital service channels, the use of modern technologies and integration with state digital platforms. It has been proven that the successful digitalization of the banking sector of Ukraine depends on the ability of financial institutions to adapt to new technologies, while ensuring a high level of security and compliance with regulatory requirements.Originality. The rationale for integrating innovative technologies, improving legislation and increasing financial literacy to achieve synergy between the financial and banking sector and FinTech has received further development, which will contribute to economic growth, increasing financial inclusion and competitiveness of Ukraine on the global market.Practical value. The results of the conducted research will enable the banking sector of Ukraine to respond adequately to the challenges posed by the digitalization of the banking business, and to realistically assess the risks associated with these challenges in order to achieve the effectiveness of the introduction of financial technologies into the practical activities of working with bank clients.Key words: digitalization, FinTech, artificial intelligence, blockchain technology, cyber security.
Keywords: digitalization; FinTech; artificial intelligence; blockchain technology; cyber security.